A widespread picornavirus affects the hemocytes of the noble pen shell (Pinna nobilis), leading to its immunosuppression - Carella, Francesca; Prado, Patricia; De Vico, Gionata; Palić, Dušan; Villari, Grazia; García-March, José Rafael; Tena-Medialdea, José; Cortés Melendreras, Emilio; Giménez-Casalduero, Francisca; Sigovini, Marco; Aceto, Serena (Frontiers in Veterinary Science, 2023)
Introduction The widespread mass mortality of the noble pen shell (Pinna nobilis) has occurred in several Mediterranean countries in the past 7 years. Single-stranded RNA viruses affecting immune cells and leading to immune dysfunction have been widely reported in human and animal species. Here, we present data linking P. nobilis mass mortality events (MMEs) to hemocyte picornavirus (PV) infection. This study was performed on specimens from wild and captive populations. Methods We sampled P. nobilis from two regions of Spain [Catalonia (24 animals) and Murcia (four animals)] and one region in Italy [Venice (6 animals)]. Each of them were analyzed using transmission electron microscopy (TEM) to describe the morphology and self-assembly of virions. Illumina sequencing coupled to qPCR was performed to describe the identified virus and part of its genome. Results and discussion In 100% of our samples, ultrastructure revealed the presence of a virus (20 nm diameter) capable of replicating within granulocytes and hyalinocytes, leading to the accumulation of complex vesicles of different dimensions within the cytoplasm. As the PV infection progressed, dead hemocytes, infectious exosomes, and budding of extracellular vesicles were visible, along with endocytic vesicles entering other cells. The THC (total hemocyte count) values observed in both captive (eight animals) (3.5 × 104–1.60 × 105 ml−1 cells) and wild animals (14 samples) (1.90–2.42 × 105 ml−1 cells) were lower than those reported before MMEs. Sequencing of P. nobilis (six animals) hemocyte cDNA libraries revealed the presence of two main sequences of Picornavirales, family Marnaviridae. The highest number of reads belonged to animals that exhibited active replication phases and abundant viral particles from transmission electron microscopy (TEM) observations. These sequences correspond to the genus Sogarnavirus—a picornavirus identified in the marine diatom Chaetoceros tenuissimus (named C. tenuissimus RNA virus type II). Real-time PCR performed on the two most abundant RNA viruses previously identified by in silico analysis revealed positive results only for sequences similar to the C. tenuissimus RNA virus. These results may not conclusively identify picornavirus in noble pen shell hemocytes; therefore, further study is required. Our findings suggest that picornavirus infection likely causes immunosuppression, making individuals prone to opportunistic infections, which is a potential cause for the MMEs observed in the Mediterranean.